REALISASI KEBIJAKAN DOMESTIC MARKET OBLIGATION BATUBARA PADA TAHUN 2018-2022 - Salman Akira Togi; Ima Mayasari (Journal Publicuho, 2023)
The purpose of this writing is to find out the Realization Of Coal Domestic Market Bondage Policy In 2018-2022. The approach used in this research is post-positivism with qualitative data collection. The research results show that the realization of DMO absorption from 2018-2022 can be considered not good. Moreover, 2021 and 2022, the annual production plan in 2021 is 625 million tons, and the DMO is 137.5 million tons, but it has not been completely absorbed, from the data obtained until the beginning of 2022, the DMO target in 2021 is only reached 21%, from the target of 22%. PLN faces a coal deficit in early 2022 and threatens 10 million families with the potential to lose electricity in early 2022. In an effort to overcome this coal deficit, the Indonesian government through the Ministry of Energy and Mineral Resources (ESDM) has implemented an export ban policy on all coal companies in Indonesia. The long step is to include additional clauses for mining companies to be more compliant with the policy so that they do not choose to pay fines.